Peran Tata Kelola dan Kepatuhan dalam Manajemen Risiko pada Perbankan Syariah - Rahma Zhafirah; Fauzatul Laily Nisa (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Currently, sharia banking is developing rapidly as an alternative to conventional banking systems based on sharia principles. However, as sharia banking develops, new challenges emerge that require the implementation of effective risk management. Existence risk management is very important to avoid losses arising from not complying with sharia regulations and principles. The aim of writing the research is to examine the role of governance and the existence of risk management in Islamic banking. This research applies a qualitative descriptive approach by applying library research methods using secondary data originating from articles, research results and references related to the researcher's topic. The research results show that the role of governance and maintenance in risk management in sharia banking is very important to ensure operations comply with sharia principles and industry standards. Good governance increases transparency, accountability and operational integrity, while maintaining sharia law and banking regulations, reducing legal and reputation risks so that it can achieve stability and extinction in its operations.